2017
DOI: 10.1096/fj.201601240r
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of Musashi‐2, Numb, MDM2, and P53 in drug resistance and malignant biology of pancreatic cancer

Abstract: Our earlier work showed that Musashi (MSI)-2 promoted the development of pancreatic cancer (PC) by down-regulating Numb, which prevented murine double-minute (MDM)-2-mediated p53 ubiquitin degradation. Thus, we investigate the relationship among MSI2, Numb, MDM2, and p53 in PC and, an association that has not been reported to our knowledge. MSI2 had no relationship with mutant p53 (mtp53) and wild-type p53 (wtp53) in normal PC cells. However, in response to gemcitabine or cisplatin treatment, MSI2 silencing si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 39 publications
(65 reference statements)
9
54
0
Order By: Relevance
“…Consistent with our previous studies [21,23], Numb knockdown significantly reversed the increase in wtp53 protein levels induced by silencing SRPK2 during oxaliplatin treatment in Capan-2 and SW1990 cells ( Fig. 7).…”
Section: Srpk2 Regulated Cell Migration Invasion and Chemosensitivitsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with our previous studies [21,23], Numb knockdown significantly reversed the increase in wtp53 protein levels induced by silencing SRPK2 during oxaliplatin treatment in Capan-2 and SW1990 cells ( Fig. 7).…”
Section: Srpk2 Regulated Cell Migration Invasion and Chemosensitivitsupporting
confidence: 92%
“…SRPK2 silencing significantly enhanced the level of Numb protein in PC cells (Fig. A,B), and our previous studies showed that Numb knockdown downregulated the wtp53 protein during chemical agent treatment . Thus, we inferred that silencing SRPK2 upregulated the oxaliplatin‐induced wtp53 activation via upregulating Numb protein.…”
Section: Resultssupporting
confidence: 70%
“…Despite the challenges for in vivo administration, we reduced the disease burden in an aggressive MLL-AF9 leukemia model and decreased MYC levels without overt toxicity. Interestingly, it has previously been shown that MSI2 can contribute to chemotherapeutic resistance in different cancer models 42,55,56 . Future studies could examine if combination therapies could provide additional clinical benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence polarization (FP) assays and calculation for the Kd were carried out using our previously described methods. 26 RNA with scrambled sequence was used as the control (control 15 ). All RNAs were used at 2 nM.…”
Section: Fluorescence Polarization Assaymentioning
confidence: 99%
“…The RNA-binding protein (RBP) Musashi-2 (MSI2) is overexpressed in many cancers, including colorectal adenocarcinomas, 1-3 breast, 4,5 hematologic malignancies, [6][7][8][9][10][11][12] lung, 13 glioblastoma, 14 and pancreatic cancers. [15][16][17] As such, it mediates mRNA stability and translation of proteins involved in oncogenic pathways. [18][19][20] Overexpression and knockdown studies indicate that MSI2 is a promising therapeutic target for cancer.…”
Section: Introductionmentioning
confidence: 99%